Oncological outcomes after endoscopic removal of malignant colorectal polyps - Gonçalves, BM; Fontainhas, V; Caetano, AC; Ferreira, A; Gonçalves, R; Bastos, P; Rolanda, C (My University, 2013)
Objective: malignant colorectal polyp, defined by submucosally invasive adenocarcinoma, is the earliest form of clinically relevant colorectal cancer (CRC). After endoscopic resection additional surgery may be necessary, although decision criteria remain debatable. The objective of this study was to assess oncologic outcomes in terms of locoregional disease and to identify areas of improvement that may facilitate patients´ management.Methods: retrospective study of 40 patients with T1 CRC endoscopically resected between 2007 and 2012. Clinicopathological features were assessed and correlated with residual disease (RD), defined as presence of adenocarcinoma in intestinal wall and/ or lymph nodes.Results: thirty-one patients underwent surgery while 9 were followed-up. After surgery, RD was confirmed in 15 (48.4 %) patients: 8 (53.3 %) wall disease, 5 (33 %) nodal metastasis, and 2 (13.3 %) with both. No recurrence was detected in the follow-up group. The characteristics of the lesions that were associated with DR were sessile configuration (p = 0.03), the degree of differentiation G3 (p = 0.01) and intercepted/indeterminate margins (p = 0.01). Twenty-two patients were operated because of inadequate evaluation, mainly due to piecemeal resection, and half of them were disease free. Postoperative complications were found in 9 (30 %) patients, mainly anastomotic leakage that was associated with rectum anterior resection (p = 0.03).Conclusions: surgery should be considered in the presence of any risk factor for residual disease, while follow-up can be offered in low risk settings. Was also demonstrated a clear need for technical improvement in endoscopic resection and pathology evaluation in order to prevent unnecessary surgeries.
Keywords: Pólipos do Colon; Neoplasias Colorrectais; Endoscopia